Graduated compression stockings: Physiological and perceptual responses during and after exercise - Ali, A.; Caine, M. P.; Snow, B. G. (Journal of Sports Sciences, 2007)
The aim of this study was to examine the effect of wearing graduated compression stockings on physiological and perceptual variables during and after intermittent (Experiment 1) and continuous (Experiment 2) running exercise. Fourteen recreational runners performed two multi-stage intermittent shuttle running tests with 1 h recovery between tests (Experiment 1). A further 14 participants performed a fast-paced continuous 10-km road run (Experiment 2). Participants wore commercially available knee-length graduated compression stockings (pressure at ankle 18 - 22 mmHg) beneath ankle-length sports socks (experimental trials) or just the latter (control trials) in a randomized counterbalanced design (for both experiments). Results: No performance or physiological differences were observed between conditions during intermittent shuttle running. During the 10-km trials, there was a reduction in delayed-onset muscle soreness 24 h after exercise when wearing graduated compression stockings (P < 0.05). There was a marked difference in the frequency and location of soreness: two participants in the stockings trial but 13 participants in the control trial indicated soreness in the lower legs. Conclusion: Wearing graduated compression stockings during a 10-km road run appears to reduce delayed-onset muscle soreness after exercise in recreationally active men.